The employment of learning strategies in learning engineering terminology among engineering undergraduates - Amri Muaz, Azmimurad; Najah, Osman (Readers Insight Publisher, 2019)
This research reports on a mixed method study with the aim to discover the employment of vocabulary learning strategies by students majoring in engineering course in learning technical vocabulary which is in this context, the engineering terminologies. This research adopted Explicit Vocabulary Learning Theory by Ellis (1994) which proposed that there are usage of learning strategies in the process of learning word meanings. Five vocabulary learning strategies taxonomies were employed in this study which were developed by Schmitt (1994) which are determination, social, memory, cognitive and metacognitive strategies. Each taxonomy has a few strategies that are developed specifically according to the type of strategies used. All five taxonomies of vocabulary learning strategies were compared to the students’ field of study, year of study and English proficiency level. Previous studies highlighted that there were differences found in the use of strategies among learners in comparison to their characteristics.